The influence of brand on shopping at Melaka Mall Sdn Bhd / Muhammad Iberahim - Iberahim, Muhammad (Faculty of Business and Management, 2014)
Brand is one of the most important aspects of any business, large or small, retail or Business to Business (B2B). The present harsh business climate has forced companies to consider branding efforts, in order to stay competitive. The gap between main and small actors on the market is increasing, which makes it crucial for weaker brands to develop an effective branding strategy. Nowadays, customers are very deeply connected to the brands. When they purchase any product like a car, mobile, items of daily need, even a shopping place, brand name influence the consumer’s choice. Some customers purchase the specific branded things just due to the brand name. Customers believe that brand name is a symbol of quality, status and become a part of their life. The aim of this research is to provide a better understanding about the influence of brand on shopping at Melaka Mall. This research explores, describes and tries to explain the influences of brand on shopping, how the brand influence customers and how customers describe the brand based on three variable of brand which are brand loyalty, brand awareness and brand association. This research has conducted at Melaka Mall SDN. BHD and data was primarily collected through a questionnaire. The data obtained from the questionnaires are being analyzed by using SPSS 14.0.